Da frase ao inconsciente: a escrita e os efeitos do significante - Palmeira, Juljan Lima (2009)
This work intends to present the way the traditional grammatical analysis of the sentence is presented. It will stablish a comparison between the sausserean theory of the sintagmatical and paradigmatical relations with concepts from lacanian psychoanalysis. Among lacanian concepts presented here, the one which defines the signifier as a responsible for effects of signified is emphasized. According to what could be observed, the signifier has a major function both in the sentence as in the unconscious structure, taking into account that both fields have an essentially different way of looking at the signifier. Considering that speech, main psychoanalysis object, is structured through sentences and that through speech psychoanalysis is able to investigate the signifier action in the constitution of the subject, the differences between these two fields of knowledge in describing the sentence structure taking into account the subjective constitution of the sentence were observed.